Analysis of Perceived Usefulness Perceived Ease of Use and Social Influence by Mediating Attitudes Towards Intention to Purchase Excess Food Through Surplus Application - Chika Retno Astriani; Janfry Sihite (Indonesian Journal of Business Analytics, 2025)
Using the Surplus application, this study examines how users' suboptimal food purchase intentions are influenced by attitude, perceived utility, perceived ease of use, and social impact. 105 citizens of DKI Jakarta, Banten, and West Java who had downloaded but never used the Surplus app participated in the study. Purposive sampling and quantitative non-probability sampling were both employed in the study. The Structural Equation Modeling–Partial Least Square (SEM-PLS) approach was used to evaluate the data. The findings indicated that purchase intentions were positively but marginally impacted by perceived utility and perceived simplicity of use. Nonetheless, it has been demonstrated that attitudes and social influence significantly and favorably affect consumers' intentions to make purchases. Furthermore, attitude was positively and significantly impacted by social influence, perceived utility, and perceived simplicity of use. This study also demonstrates how attitude mediates the relationship between social influence, perceived utility, and perceived ease of use and purchase intentions. By encouraging reduced food waste, the Surplus app in particular has a noble goal of protecting the environment. The results of the study shed insight on factors that affect customers' choices to buy less-than-ideal food.